Lateral thoracotomy for epicardial pacemaker placement in patients with congenital heart disease. (2nd January 2018) - Haight, Paulina J; Stewart, Robert E; Saarel, Elizabeth V; Pettersson, Gosta B; Najm, Hani K; Aziz, Peter F
Abstract: OBJECTIVES: Our institution adopted a lateral thoracotomy approach to epicaridal pacemaker implantation with the objective of avoiding epicardial scar tissue and to achieve adequate lead pacing and sensing. We sought to assess the short-term outcomes of this approach. METHODS: A single-centre review was conducted in paediatric patients and adults with congenital heart disease or inherited arrhythmia syndromes who underwent a lateral thoracotomy for epicardial pacemaker placement from August 2010 to January 2016. Patient histories were recorded along with outcomes including complications, lead and generator performance. RESULTS: Twenty-one operations were performed in 20 patients (median age 17 years, range 3 months–49 years), including 19 pacemakers and 2 implantable–cardioverter defibrillators (ICDs). Prior epicardial pacemakers had been placed in 11 (55%) patients, including 3 with multiple pacemakers. Most patients had undergone at least 1 prior cardiac operation, with a mean of 3.2 (range 0–7) prior cardiac operations. Through our lateral thoracotomy approach, 17 of the 19 attempted atrial leads (89%) and 20 of the 20 attempted ventricular leads (100%) were successfully implanted with acceptable pacing thresholds. Complications included 1 (5%) bleeding, 2 (10%) pacemaker pocket revisions and 1 late death at 6 months unrelated to the pacemaker. There were no lead failures at a mean follow-up period of 27.5 months (range of 0.7–56.1 months). CONCLUSIONS: The lateral thoracotomy is a useful approach for epicardial pacemaker implantation in patients with congenital heart disease or inherited arrhythmia syndromes including those with multiple prior operations.